Synthesis of PbS/Ni2+ doped CdS quantum dots cosensitized solar cells: Enhanced power conversion efficiency and durability. (10th August 2015) - Chen, Yanli; Tao, Qiang; Fu, Wuyou; Yang, Haibin
Highlights: The synthetic of PbS/NCdS/TiO2 photoanode with a simple method. The power conversion efficiency of the PbS/NCdS/TiO2 is 3.60 %. The effects of photovoltaic performances caused by doped with Ni 2+ were studied. ZnS passivation layer enhanced electron lifetime significantly. Ni 2+ doped CdS is an effective way to enhance the energy conversion efficiency. Abstract: A new photoanode by employing Ni 2+ doping of CdS used to fabricate PbS and Ni 2+ doped CdS cosensitized quantum dot-sensitized solar cell (QDSSCs). Under AM 1.5 G (100 mW/cm 2 ) illumination, the cell device exhibit a power conversion efficiency (η) of 3.60 %, which is higher than the value of 2.65 % obtained with CdS without dopant. The improved photoelectric performance is due to the impurities from Ni 2+ doping of CdS, which have an impact on the electronic and photophysical properties, and the dopant creates electronic states in the midgap region of CdS thus altering the charge separation and recombination dynamics. Furthermore, the cell device based on the Ni 2+ doped CdS photoanode shows superior stability in the sulfide/polysulfide electrolyte, resulting in a highly reproducible performance, which is a serious challenge for the Ni 2+ doped solar cell. This finding can provide an effective method for the fabrication of new photoanode, which can pave the way to further improve the power conversion efficiency of the future QDSSCs.